Effect of a partial cage dividing enrichment on aggression-associated parameters in group-housed male C57BL/6NCrl mice - Mertens, Sinja; Gass, Peter; Chourbaji, Sabine (Applied animal behaviour science, 2020)
Group-housing is highly important for social animals. Group-housing of male mice in captivity though often leads to aggression with partially disastrous consequences for the animals as well as for the quality of experimental data. In this study we investigated the effect of a novel “cross-enrichment”, i.e. a colored partial cage divider, which is provided in transparent or black and which is partly separating the cage in four small areas. Group-housed male C57BL/6NCrl mice (three per cage) were maintained under either standard conditions (nestlet group) or enriched conditions (nestlet + cage divider in black [EB-group] or in transparent [ET-group]) for eight weeks. Several physiological parameters (body weight, blood glucose, stress induced hyperthermia, fecal corticosterone metabolites and organ weights) and behavioral tests (Nest test, Openfield/social Novel-Object, Dark-Light-Box, Hotplate and Resident-Intruder test) were measured/performed to determine enrichment-induced effects. In comparison to nestlet- and ET-group animals, EB-mice showed significant increased stress-associated parameters, i.e. in the blood glucose concentration. Furthermore, EB animals seemed to have enhanced emotional stress with a poorer outcome in the nest test and a higher amount of fecal boli at the end of the social Novel-Object test. Additionally, EB-mice behaved more aggressively towards conspecifics after cleaning cages. We conclude that the opacity of the tested partial cage dividers has a huge impact on aggressive behavior and therefore may lead to significant changes in behavioral and physical measures potentially altering research outcomes.